A personal perspective on pedagogical structures and strategies that uphold Indigenous ways of knowing. Issue 2 (1st October 2021) - Nabaggala, Justine
This article gives a brief background of where I come from and how my experiences in Africa and North America have framed the 'philosophy of teaching' that defines me as a visual art educator. I reflect on the postcolonial concept of 'decolonization' as a means to identifying possible pedagogical alternatives of practice. Acknowledging that my knowledge embraces both 'western' and 'Indigenous' ways of knowing, poses a question for me as an art educator about ways to design and implement pedagogies that embrace contextualized experiences in order to achieve meaningful learning within formal education. I conclude by stating that nothing will effect change within Uganda's education sector, particularly in reference to visual art education and practice, without educators having a firmer grasp of their scholarly standpoint on knowledge and learning. Development of concrete ways of bringing together diverse ontological, epistemological and axiological positions of western and Indigenous knowledge systems as well as art pedagogies to facilitate learning, will require educators to develop structures and strategies that progress from the bottom up in order to benefit from the values, beliefs and ways of knowing within diverse local communities.